Pengaruh Video Animasi “Menstruasi” Terhadap Pengetahuan Dan Sikap Siswi Sekolah Dasar Dalam Menghadapi Menarche - Hartati Hartati; Wahyudi Wahyudi; Handoyo Handoyo (JURNAL KEPERAWATAN MERSI, 2019)
Menarche for women is a sign that someone is entering puberty or adolescence which is marked by changes physically and mentally. Young women who do not have proper preparation about menarche tend to show negative attitudes, such as excessive emotions, fear and confusion.This study aims to determine the effect of menstrual videos on the knowledge and attitudes of elementary school students in dealing with menarche.This type of research is quantitative research Quasi Experimental using design pre and post test design with control group. The population in this study were all students in grades V and VI in SDN Mersi 3 Purwokerto. The sampling technique is simple random sampling on students who have not experienced menarche. The instrument used to assess the level of knowledge and attitudes is a questionnaire. To analyze the effect of animated videos on the knowledge and attitudes of elementary school students in dealing with menarche is using Wilcoxon Signed Rank Test and Mann-Whitney U.The results showed that there was a significant effect of animation video on the level of knowledge of female students in the treatment and control groups (p=0,000 α=0,050) but there was no significant effect on the attitudes of students in the control group (p=0,000 α=0,055). Based on Mann-Whitney U test showed that treatment group (animation video) is more effective than control group with p=0.000 to increase knowledge and attitude menarche. The conclusion in this study is that there is a significant effect of animation video on the level of knowledge and attitudes of V and VI students in SDN Mersi 3 Purwokerto.